2014
DOI: 10.1002/jsfa.6654
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic content and ferric reducing–antioxidant power of cow's milk produced in different pasture‐based production systems in southern Brazil

Abstract: Our results revealed that, under the conditions prevalent in southern Brazil, since the cows were allowed to graze in all of the systems, the TPC and antioxidant capacity of the milk samples showed minimal variation. However, since the forage TPC and FRAP values for the milk were correlated, TPC appears to be a promising variable for the purpose of monitoring forage prior to its selection aimed at enhancing the antioxidant activity of milk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 28 publications
0
24
0
1
Order By: Relevance
“…Both systems produce a similar amount of OC on a dry matter (DM) basis but two-phase OC has approximately 4 to 5 and 2 to 3 fold higher sugar and total phenolic (TP) compounds, respectively [8], since two-phase system does not produce vegetation water during the oil extraction that three-phase system produces. Elevated TP in dairy milk, associated with the intake of feed sources that are rich in TP were reported by Kuhnen et al [9] and Kälber et al [10]. These studies suggest that feeding dairy animals with feed sources rich in TP has a potential to increase milk TP depending on the nature of TP.…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…Both systems produce a similar amount of OC on a dry matter (DM) basis but two-phase OC has approximately 4 to 5 and 2 to 3 fold higher sugar and total phenolic (TP) compounds, respectively [8], since two-phase system does not produce vegetation water during the oil extraction that three-phase system produces. Elevated TP in dairy milk, associated with the intake of feed sources that are rich in TP were reported by Kuhnen et al [9] and Kälber et al [10]. These studies suggest that feeding dairy animals with feed sources rich in TP has a potential to increase milk TP depending on the nature of TP.…”
Section: Introductionmentioning
confidence: 73%
“…Thus, transfer of phenolic contents to milk is very important as these phenols contain high antioxidant properties [2526]. The increase in TP was reported by Kuhnen et al [9] in milk of cows that were fed pasture rich in TP. Similarly, Kälber et al [10] reported an increased TP in cow milk that was obtained from animals that consumed diets containing chicory and buckwheat.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, as expected, FRAP values and TPC data of aqueous-organic extracts showed lower values in UHT cow milk than soy-based beverages ( Table 1 ). This is probably due to the profile in bioactive components of milk [ 25 , 27 ], food matrix of animal origin characterized by a small amount of polyphenols compared to those of vegetable origin.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, although this is not a direct focus of the present review, the effect of the animal origin, genetic type (i.e. breed) (10) , feed (for example, composition, quantity, and complementation, such as the fat quality) and pasture conditions (for example, organic v. conventional, seasonal variations) on the antioxidant potential of milk has been repeatedly studied (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23) .…”
Section: Introductionmentioning
confidence: 99%